ANTIBACTERIAL ACTIVITY OF AKAR KUNING (ARCANGELISIA FLAVA) SECONDARY METABOLITES: MOLECULAR DOCKING APPROACH - Fadhil Pratama, Mohammad Rizki; S, Suratno; Mulyani, Evi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Akar kuning (Arcangelisia flava) was known to have various pharmacological activities including as antibacterial. Several Gram-positive and Gram-negative bacteria show response to akar kuning secondary metabolites, although the type of metabolites that inhibit the growth of each type of bacteria not yet known. This study aims to obtain the prediction of metabolites from akar kuning with the greatest antibacterial potential against various types of antibacterial receptors. Methods: Molecular docking was performed using Autodock Vina 1.1.2 on several secondary metabolites of akar kuning against active site of several antibacterial receptors that were known for many antibiotics including as cell wall, protein, nucleic acid synthesis inhibitors, and antimetabolites. The main parameter used was the free energy of binding as affinity marker. Results: The docking results show that among 11 metabolites studied, 6-hydroxyfibraurin, berberine, and fibleucin provided the lowest free energy of binding between 11 antibacterial receptors compared with natural substrates or inhibitors from each receptor. Interesting results show by berberine as inhibitor of protein synthesis with possibility of allosteric site discovery. Berberine also shows more than 75% similarity with natural substrate of cell wall inhibition receptor, indicating possible similar type of interaction. Conclusion: Overall, it seems that for the selected secondary metabolites of akar kuning, the main mechanism of action was the inhibition of protein and cell wall synthesis, which was shown by berberine.